A analisis fungsi sastra lisan pada mantra mantra di desa tanjungan - Sholihah, Siti Thufatus (Signifiѐ, 2024)
Abstract: Oral literary works are born from culture, but literary works are written works that contain a lot of meaning and function which can be made into an honor in itself for oral literary works. from literary works is a form of public trust in tanjungan village, namely they still believe in beliefs from ancient times until now, namely the dimension of treatment for animals, namely cows, in the article now our life is modern, there are still sophisticated alternatives, but the people in tanjungan village are very thick and close to the dimensions of belief and all the majority in the village are very strongly attached to these beliefs.